2014
DOI: 10.1099/mic.0.070672-0
|View full text |Cite
|
Sign up to set email alerts
|

Pore-forming pyocin S5 utilizes the FptA ferripyochelin receptor to kill Pseudomonas aeruginosa

Abstract: Pyocins are toxic proteins produced by some strains of Pseudomonas aeruginosa that are lethal for related strains of the same species. Some soluble pyocins (S2, S3 and S4) were previously shown to use the pyoverdine siderophore receptors to enter the cell. The P. aeruginosa PAO1 pore-forming pyocin S5 encoding gene (PAO985) was cloned into the expression vector pET15b, and the affinity-purified protein product tested for its killing activity against different P. aeruginosa strains. The results, however, did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 36 publications
1
70
0
Order By: Relevance
“…It typically concerns outer membrane proteins (OMPs) involved in the uptake of iron via siderophores: type I ferripyoverdine transporter FpvAI for pyocins S2, S4, and SD2 (1719), type II ferripyoverdine transporter FpvAII for pyocin S3 (20), and ferripyochelin receptor FptA for pyocin S5 (21). Some S pyocins carry (almost) identical amino-terminal regions and basically differ only in their toxin-immunity module, emphasizing the peculiar modularity of these allelopathic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It typically concerns outer membrane proteins (OMPs) involved in the uptake of iron via siderophores: type I ferripyoverdine transporter FpvAI for pyocins S2, S4, and SD2 (1719), type II ferripyoverdine transporter FpvAII for pyocin S3 (20), and ferripyochelin receptor FptA for pyocin S5 (21). Some S pyocins carry (almost) identical amino-terminal regions and basically differ only in their toxin-immunity module, emphasizing the peculiar modularity of these allelopathic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…E-type colicins parasitize the vitamin B 12 receptor, BtuB, as their primary receptor in the outer membrane [9] and the Tol-Pal complex in the periplasm [5]. S-type pyocins S2 and S5 bind FpvA and FptA, respectively, which import siderophore-chelated iron [10,11]. How they translocate across the outer membrane is not known, although pyocin AP41, the receptor of which has yet to be identified, may translocate into cells via the Tol-Pal system [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bakkal et al (2010) have reported that bacteriocins produced by Pseudomonas and Burkholderia strains have intra-and interspecies bacteriocin-like inhibition ability within the CF lung (Bakkal et al, 2010). Some of these bacteriocins, such as the Pseudomonas pyocin, share the same receptors as siderophores (Denayer et al, 2007;Elfarash et al, 2014) and therefore interfere with iron acquisition of their target host. It has also been demonstrated that P. aeruginosa can lyse Staphylococcus aureus using PqsA, a coenzyme ligase, to gain access to internalized iron (Mashburn et al, 2005).…”
Section: Pathogen Interactions and Competition For Iron In Cfmentioning
confidence: 99%